Charisiana iV: ¿inavratae o inavrate? Vaivenes de una Variante (Char. gramm. p. 262, 27-8) - Javier Uria Varela; Marcos Antonio Pérez Alonso (Exemplaria Classica, 2014)
This paper deals with some shocking nom- inal items in a list of adverbs in Charisius’ ars grammatica. We pay particular at- tention to the lemma inaurate, subject to controversy from the beginning of the tex- tual transmission. We provide a coherent picture in terms of both textual criticism and the grammatical tradition.